Mediating Role of Social Competence in the Relationship between Tendency to Cosmetic Surgery and Psychological Capital in Women Applying for Cosmetic Surgery - Naghmeh MalekMohammadi; Sara Hashemi; Javad Rahmati (Iranian Evolutionary Educational Psychology Journal)
Objective: The objective of the present study was to examine the mediating function of social competence within the association between the inclination towards cosmetic surgery and psychological capital among women seeking cosmetic surgical procedures. Methods: The methodological approach employed was a descriptive correlational design predicated on structural equation modeling. The statistical population encompassed all women who sought cosmetic surgery at cosmetic surgery centers located in Tehran (specifically regions 1, 2, 3, and 6) during the year 2023, from which a sample of 285 individuals was purposefully selected in accordance with predefined entry and exit criteria. For the purpose of data collection, the questionnaires devised by Etemadifard and Amani (2013) regarding the propensity for cosmetic surgery, Luthans et al. (2007) pertaining to psychological capital, and Felner (1990) concerning social competence were utilized; furthermore, the regression analysis technique was employed for data evaluation utilizing SPSS28 software. Results: The results indicated that the coefficient associated with the indirect effect of psychological capital on the inclination towards cosmetic surgery, mediated by social competence, was statistically significant (p<0.05). Consequently, it may be inferred that individuals possessing higher levels of psychological capital exhibit a reduced tendency towards cosmetic surgery, with social competence serving as a crucial mediator in mitigating this inclination. Conclusions: Consequently, the outcomes of this research may assist policymakers, scholars, and practitioners within the realms of health and psychology in formulating effective strategies aimed at diminishing the propensity for cosmetic surgery while enhancing the mental and physical well-being of individuals.